PEDAGOGICAL TACT AS A COMPONENT PEDAGOGICAL CULTURE (Pedagogy of Higher and Secondary Education, 2007)
This article is about pedagogical tact wich descreig as a sense ofpedagogical measures, that guarantee supply of effective pedagogical links and pedagogical culture.